Un second point de vue juridique - Plamondon, Luc (Assurances)

(untitled) (HEC Montréal, 1988)
In this article, Mr. Luc Plamondon, a jurist working in the legal department of an insurance company, shares with us his thoughts on various aspects of the AIDS problem: human rights, insurance policies and the law on insurance. For example, he explores the obligation of the applicant to declare the risk, the obligation of the insurer to make insurance available to him and the right of the insurer to set an appropriate rate for the premium, to ask certain questions or to request specific tests.